Gender crime convergence over twenty years: evidence from Australia - Beatton, Tony (European economic review, 2018)
Historically men have been responsible for the majority of criminal activity and dominate prison populations around the globe. The twentieth century witnessed significant male–female convergence in a myriad of positive dimensions including human capital acquisition, labour force participation and wages. This has prompted the question, to what extent are women ‘looking more like men’? In this paper we examine whether similar forces are at play in the context of criminality. We study the pattern of gender convergence in crime using rich administrative data on the population of young people in Queensland, Australia. The evidence points to a significant narrowing of the gender gap in criminal activity over the course of the last twenty years. Crime convergence occurs for broad aggregates of both property and violent crime, as well as for almost all sub-component categories. Convergence occurs largely because crime has fallen significantly for men, combined with no downward trend for women. This is confirmed by aggregate analysis of rates of offending in police force districts matched to Census data by gender between 2001 and 201